Measurement of dynamic characteristics of a steel-spring floating slab track and a monolithic roadbed track in a subway tunnel - Yongjian Zhou; Guan Xu; Tao Sheng; Hu Jiang; Chao Jin (Journal of Asian Architecture and Building Engineering)
Dynamic characteristics including wheel–rail interactions and vibration-damping effects of a steel-spring floating slab track were measured and compared with those of a monolithic roadbed track. These two tracks are in the same subway tunnel, and with similar conditions. Measuring results show that the vertical and transverse wheel-rail forces on the floating slab track were separately 8% and 47% larger than those on the monolithic roadbed track. Due to the increased quasi-static wheel-rail forces, vertical and transverse rail deformations on the floating slab track were separately 2.5 and 4 times larger than those of the monolithic roadbed track. Based on the measured acceleration vibration levels, the vertical and transverse vibrations of the tunnel wall of floating slab track were 5 dB smaller than those of the monolithic roadbed track. Meanwhile, the vibrations of the floating slab were 10 dB larger than those of the monolithic roadbed. Therefore, the floating slab effectively blocked vertical and transverse energy transmissions. Based on the measured frequency-division vibration levels, vertical and transverse resonant vibrations of the tunnel wall of floating slab track were 15–22 dB smaller than those of monolithic roadbed track. However, low-frequency wheel-rail forces increased vibrations from 1 to 20 hz, which may have a negative influence on soil ground vibrations.